APLIKASI GEOMAGNET UNTUK EKSPLORASI BIJIH BESI DI DAERAH KACANG BOTOR, KABUPATEN BELITUNG BARAT - Zaidan, Moh (Badan Pengkajian dan Penerapan Teknologi, 2009)
Iron ore is one of commodity of metallic mineral that is located in Belitung Barat, Bangka Belitung Province. Existence of iron ore can be detected by applying a technology of geomagnet exploration using a magnetic characteristic of iron ore at study area. In this paper, it will be discussed about application of geomagnet for exploring iron ore at Kacang Botor area. Based on result of Geomagnet measurement and data processing, it can be interpretated that Kacang Botor area has prospect of iron ore (Fe) reserve, where contur of magnetic anomaly has a value of about 500 nT - 4000 nT. In a ddition, it can be predicted that iron ore at this area point to type of vein with direction of its distribution is west – east. This fact is suitable with commonly linement of iron ore deposit in belitung island.